The Formulation of a Serum Containing Tomato (Solanum Lycopersicum L.) Extract for a Green Anti-Aging Skincare Product - Nguyen, Van Quy; Lau, Thieu Phu; Huynh, Thi Kim Chi; Nguyen, Hoang Phuc; Nguyen, Thi Cam Thu; Nguyen, Thi Hong An; Nguyen, Xuan Ngoc; Hoang, Thi Kim Dung; Ton, Anh Khoa (Journal of Technical Education Science, 2024)
Sunlight exposure can lead to photoaging that reduces the quality of life, from inside to outside. Tomato contains a lot of nutrients and valuable compounds which are powerful antioxidants. Hence, the utilization of safe and effective natural compounds for the creation of phytocosmetic is undoubtedly attractive for sustainable development. Herein, the small pieces of tomato were dried at 60oC for 6 hours to remove the water. The chloroform solvent was used for extraction by a 1:10 (w/v) ratio for 24 hours without light exposure. The yield was 0.273% compared with the dry tomato. Besides, the total polyphenol and flavonoid contents were 111.49 ± 0.31 μg gallic acid equivalents/mg extract and 150.15 ± 2.17 μg quercetin equivalents/mg extract, respectively. The anti-aging serum containing 0.10% tomato extract was an ideal topically phytocosmetic that was stable after physical evaluations, had no irritation by voluntary assessment as well, and had a uniform diameter of O/W droplet around 40 µm with a potential antioxidant for daily application. Therefore, we have formulated an anti-aging serum containing tomato extract for nourishing the outside beauty and taking care of inside health.